Adoption of Improved Buffalo Husbandry Practices in Peri-Urban Areas of Surat City, Gujarat (Indian Journal of Animal Production and Management, 2024)
The present study was carried out in the peri urban areas of Surat city of Gujarat to find out the  adoption of improved buffalo husbandry practices.  A random sample of 50 buffalo farm owners were  selected and interviewed for the interview schedule  prepared about adoption of improved dairy  husbandry practices in six major aspects of  housing, feeding, breeding, health care, milking and  calf rearing management was studied. Housing in  separate located place (100%), providing proper  floor space (98%) and proper height and ventilation  (90%) were more adopted in housing practices.  Provision of clean and fresh drinking water (100%),  feeding extra ration to advance pregnant animals  (64%) and feeding balance concentrate mixture on  the basis of milk production (64%) were more  adopted in feeding management. In adoption of  breeding management, keeping watch on oestrus  cycle and heat symptoms of animals (100%),  artificial insemination of animals (100%) and  practicing pregnancy diagnosis between 60-90  days after service (91%) were more adopted by  buffalo owners. Observing animals daily for signs of  sickness (100%), timely and regularly vaccination  (100%) and treatment of reproductive disorders  (75%) were more adopted by respondents in health  care management practices. In milking and calf  rearing practices, washing pails and hands before  milking (100%) and regularity in milking time  (100%), early solid feeding (100%) and milk feeding  to calves up to three months of age (96%) were  more adopted by the buffalo owners.
Keywords: adoption; buffalo; buffalo husbandry practices; peri-urban areas; Surat